Investigating the Association between Preterm Birth and Fetal Characteristics with Seasonal Variation - Darvish, Soodabeh; Karbaschi, Roxana; Jafari, Aram (Advances in Nursing & Midwifery, 2024)
Introduction: Premature birth (PTB) is a common cause of infant mortality and can lead to long-term complications and disorders. Considering that the prevalence of PTB may vary in the seasons, the changes in preterm birth rates during the seasons were investigated in this study, along with exploring the factors affecting the occurrence of preterm births. Methods: In this cross-sectional study, data collected from pregnant women at Taleghani Hospital to investigate 140 cases of preterm births, concentrating on seasonal differences, maternal age, gravidity, previous abortion history, newborn gender, weight, umbilical cord pH, and the Apgar score measured at ten minutes birth. Results: The study found that preterm birth rates vary by season, peaking in autumn at 29.3% and dropping to 19.5% in winter. The gender distribution of preterm infants was nearly equal, with a slight majority of boys. The average gestational age of mothers remained stable across seasons, and there was no significant difference in average baby weight among different maternal age groups. The average umbilical cord artery pH was 7.26, and the mean birth weight was 2,223 grams. Additionally, Spearman’s analysis showed a positive correlation between gestational age and both ten-minute Apgar scores and birth weight. However, no significant associations were found between umbilical cord artery pH and gestational age, delivery type, or infant gender. Conclusions: Preterm birth rates are not significantly affected by seasons, while longer gestational periods lead to heavier newborns and better Apgar scores. Umbilical cord pH remains unaffected by gestational age, delivery method, or baby gender.